Identifikasi Pemanfaatan Hutan Mangrove oleh Masyarakat Studi Kasus Hutan Mangrove Pulau Sicanang, Belawaan Pulau Sicanang, Kota Medan, Sumatera Utara - Manik, Irene Anggreny Br.; Purba, Miranda; Harefa, Meilinda Suriani; Hutagalung, Galatia Valentin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesia is the largest archipelagic country in the world, with a land area that includes rich coastal ecosystems, including mangrove forests. Mangrove forests in Indonesia have a very important ecological role, such as protection against coastal abrasion, habitat for marine biota, and carbon absorption. However, these forests face threats due to land conversion for agriculture, housing, and industry. This study aims to explore the utilization of mangrove forests on Sicanang Island, Medan, with a focus on the social and economic impacts on local communities. The results of the study show that the community utilizes mangrove forests for fisheries, shrimp farming, and the use of raw materials for daily needs. Sustainable management of mangrove forests is very important to maintain the balance of the ecosystem and improve the quality of life of coastal communities.